PENGARUH PENERAPAN LATIHAN KECEPATAN (FILE RELAY) TERHADAP KECEPATAN SISWA EKSTRAKURIKULER BOLABASKET SMA NEGERI 1 SALO KABUPATEN KAMPAR - Permana, Harry; Slamet, Slamet; Nita Wijayanti, Ni Putu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The problem in this research is the speed of students who take part in basketball extracurricular activities at Salo 1 High School in Kampar Regency is still not optimal, it can be seen from the slow movement of students when dribbling and changing the direction of movement in finding a position, difficult to pass the opponent when controlling the ball and it is difficult to follow or guard your opponent while defending. Therefore students who take basketball extracurricular activities at Salo 1 High School in Kampar District need to be given training on file relay speed. The purpose of this research was to determine the effect of the application of speed training (relay file) on the speed of students participating in basketball extracurricular activities at Salo 1 Public High School, Kampar Regency. The hypothesis proposed is that there is an effect of the application of speed training (file relay) on the speed of basketball extracurricular students in Salo 1 Public High School, Kampar Regency. As for the population and sample in this research were students who took part in basketball extracurricular activities at SMA Negeri 1 Salo Kabupaten Kampar, amounting to 10 people. The instrument used to collect data is the pree test and speed test post with a 30 meter run. The data analysis technique used is the t test. The results of this research indicate that the speed of students has increased from before being given a speed training (relay file) this is evidenced by the value of 9.345 which is greater than the value of ttable 1.833. So it can be said that speed training (relay file) is very suitable given to students in order to increase the speed they have so students can improve their achievements in basketball extracurricular activities.Key Words: Speed Training (File Relay), Speed